OUTLOOK FUNDAMENTALS OF THE TERM "SPIRITUALITY" INTERPRETATION BY THE UKRAINIAN EDUCATORS (THE SECOND HALF OF THE XIX CENTURY) - Olga Tsybulko ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The article deals with the ideological principles of interpretation of the term "spirituality" by Ukrainian educators of the second half of the nineteenth century. Particular attention is paid to the fundamental concepts of "spirituality" in pedagogy. The article reveals the peculiarities of the national definition of the term "spirituality".